Land Suitability for Pepper in Tanggamus Regency, Lampung Province, Indonesia - Diah Puspita Hati; Mira Media Pratamaningsih; Rufaidah Qonita Muslim; Erwinda Erwinda; Adi Setiadi; Pronika Kricella; Dwi Oksanti Saparina (Jurnal Ilmu Pertanian Indonesia, 2024)
Pepper is one of the local commodities developed in Indonesia and has become an export commodity. Improving the productivity of pepper can be done through sustainable land management based on the characteristics of soils and their potential. Therefore, land suitability evaluation is needed to maximize land potential and minimize inhibiting factors for pepper plant growth. This study evaluated the characteristics, potential, and distribution of suitable land for pepper plant development in Tanggamus Regency, Lampung Province, Indonesia. Land suitability was evaluated by matching land characteristics with land suitability criteria for pepper plants. This criterion consists of four classes, namely highly suitable (S1), moderately suitable (S2), marginally suitable (S3), and not suitable (N). The soil's climate and physical and chemical properties were the land characteristics data used. Potential land availability was arranged based on land suitability classes by considering existing land use and forest area status. Soil types in Tanggamus Regency are Inceptisols, Entisols, Alfisols, Andisols, Oxisols, and Ultisols, with the most extensive distribution of soil types being Oxisol (Typic Hapludox). The distribution of relief in Tanggamus Regency is dominated by mountainous areas with very steep slopes (slope >40%). Land suitability classes are moderately suitable (S2), marginally suitable (S3), and not suitable (N) with limiting factors, namely drainage, texture, soil pH, and erosion hazard/slope. Improvement can be made by planting according to contours, planting cover crops, applying lime and organic matter, and ensuring balanced fertilization. The development of pepper plants in Tanggamus Regency can be achieved through diversification and extensification, with a total area of potential land that can be developed of 73,995 ha. Keywords: land potential, land evaluation, limiting factor, pepper, soil characteristics